PERBEDAAN ANTARA WANPRESTASI DAN DELIK PENIPUAN DALAM HUBUNGAN PERJANJIAN - Sugirhot Marbun; Mahmud Mulyadi; Suhaidi Suhaidi; Mahmul Siregar (USU LAW JOURNAL, 2015)
ABSTRACT Breach of contract is a true realm of civil law which should not be replaced by blaming someone else who did the breach of contract under criminal law but it must be based on the civil law.The offense of fraud should not be blamed on someone who did it for acts of breach of contract because it is the domain of criminal law. But in the court practice, a dilemma in law enforcement between which act is included in the category of breach of contract and which act is included in the category of offense of fraud in a contract frequently occur. The characteristic of breach of contract is seen from the negligence of somebody inimplementaing achievement in the good faith. While the element in the offense of fraud is exactly seen from the contrary namely from the element of intent not from the element of negligence. In the court of law, the practice of breach of contract and the offense of fraud. For the characteristics of breach of contract was released by the judge seen from the longstanding trade relationship in good faith. While the characteristics of the oiffense of fraud contained the element of intent in bad faith, benefiting themselves  or others,  not performing or avoiding obligations, containing the words of lie, and delaying for no obvious reason. Therefore, every individual, the parties or communities in making an agreement, especially police officers, prosecutors, advocates, and judges need to understand the characteristics of the difference between breach of contract and the offense of fraud. In the cases of agreement with the indication of breach of contract, the negligence of debtor in paying his debt must be proven first before the debtor can be accused for having breached a contract. Whilein the cases of agreement with the indication of the offense of fraud, the element of intent in bad faith must be proven first. Keywords: Agreement, Breach of Contract, Offense of Fraud